2020
DOI: 10.1093/neuonc/noaa051
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycin D downregulates Sox2 and improves survival in preclinical models of recurrent glioblastoma

Abstract: Background Glioblastoma (GBM) has been extensively researched over the last few decades, yet despite aggressive multimodal treatment, recurrence is inevitable and second-line treatment options are limited. Here, we demonstrate how high-throughput screening (HTS) in multicellular spheroids can generate physiologically relevant patient chemosensitivity data using patient-derived cells in a rapid and cost-effective manner. Our HTS system identified actinomycin D (ACTD) to be highly cytotoxic ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Nevertheless, comprehensive information on its central nervous system (CNS) disposition is lacking. However, previous studies suggested a potential role of actinomycin D in the treatment of pediatric CNS neoplasms: Preclinical studies revealed efficacy in in vitro models of ependymoma [ 15 ] and, to a certain degree, in orthotopic mouse models of glioblastoma, medulloblastoma, and embryonal tumors with multilayered rosettes (ETMR) [ 16 , 17 , 18 ]. Therefore, our aim was to establish a suitable experimental setup to accurately determine the still unclear CNS disposition of actinomycin D. This setup combined quantification of actinomycin D by ultraperformance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) in cerebral microdialysis microsamples from freely moving mice with measurements in brain tissue and plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, comprehensive information on its central nervous system (CNS) disposition is lacking. However, previous studies suggested a potential role of actinomycin D in the treatment of pediatric CNS neoplasms: Preclinical studies revealed efficacy in in vitro models of ependymoma [ 15 ] and, to a certain degree, in orthotopic mouse models of glioblastoma, medulloblastoma, and embryonal tumors with multilayered rosettes (ETMR) [ 16 , 17 , 18 ]. Therefore, our aim was to establish a suitable experimental setup to accurately determine the still unclear CNS disposition of actinomycin D. This setup combined quantification of actinomycin D by ultraperformance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) in cerebral microdialysis microsamples from freely moving mice with measurements in brain tissue and plasma.…”
Section: Introductionmentioning
confidence: 99%
“…To further confirm the effects of SOC inhibitors on the stem cell population, the expression of SOX2 was assessed. SOX2, which is a transcription factor necessary for the maintenance of glioblastoma stem cell tumorigenic activity, is commonly used to detect the stem cell population in glioblastoma [ 32 , 33 , 34 ]. Figure 5 C illustrates that SOX2 expression was significantly decreased upon treatment with YM-58483 in all GBM cells tested and with GSK-7975A in 2 of 3 GBM cells tested, confirming a role of SOC in the maintenance or expansion of GSC.…”
Section: Resultsmentioning
confidence: 99%
“…The topic of antineoplastic repurposing will only be briefly discussed given that the mechanisms of action of these drugs against GBM are the same as their original hypothesized mechanism. Many of these agents have been investigated preclinically including hydroxyurea, actinomycin D, carmofur, eribulin and paclitaxel [ 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 ]. With regard to clinical trials, vorinostat, an antineoplastic agent used for cutaneous T-cell lymphoma, was studied in a Phase I study in combination with TMZ [ 117 ].…”
Section: Discussionmentioning
confidence: 99%